PENGARUH MODEL PEMBELAJARAN RADEC TERHADAP KEMAMPUAN BERPIKIR MATEMATIS SISWA PADA MATERI PECAHAN KELAS 6 DI SDN PARAHU 3 - Eti Susanti; Supriatna, Encep (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the RADEC (Read, Answer, Discuss, Explain, and Create) learning model on the mathematical thinking ability of 6th- grade students at SDN Parahu 3, specifically in the fraction topic. The research employed a quasi-experimental design with a pre-test and post-test control group. The sample consisted of two classes, one as the experimental group, which applied the RADEC model, and the other as the control group, which used conventional teaching methods. The research sample consisted of 60 students divided into an experimental class (30 students) and a control class (30 students). Data were collected through a mathematical thinking ability test and analyzed using validity tests, reliability tests, and inferential statistics.The data collected were analyzed using statistical methods to compare the students' mathematical thinking abilities before and after the intervention. The findings indicate that the RADEC learning model significantly enhances students' ability to think mathematically, particularly in understanding and solving problems related to fractions. These results suggest that the RADEC model is an effective strategy for improving students' mathematical thinking skills in elementary school education.